Medical - and – psychological help to cosmetological patients with disharmonic inflated self-esteem - Yudin, M. A. (Journal of Education, Health and Sport, 2017)
Introduction. Classical treatment with medications, procedures, surgery is unable to restore physical health and almost has no effect on the psychological state of a patient. This raises the question of involvement in the treatment process psychological measures, increase knowledge about the psychology of the patient, medical professionals and their interrelation during treatment. The aim: to identify the targets of psychological help for cosmetological patients with disharmonic inflated self-esteem (DISE). Contingent and methods. The study was conducted at the Medical Center "CA Clinic" ( Kyiv) during 2014 – 2016. 178 women with cosmetological problems participated in the research, among them 82 had DISE (active treatment group) and 93 had harmonic self-esteem (control group). The complex psychodiagnostic study conducted for assessment psychological state. Cosmetological patients emotional condition was studied with SCL-90-R. To study the personality characteristics, Freiburg personality questionnaire (FPI, form B) and self-esteem questionnaire by V. V. Stolin and S. G. Pantileyeva were used, behavioral patterns have been investigated with S. Lazarus and Folkman’s method of WCB. Psychosocial sphere was assessed with test for diagnosis of interpersonal relations by T. Leary and social and psychological adaptation by K. Rogers and R. Diamond. Results. DISE patients complete a specific group of patients who seek for cosmetic help. Skin pathology and outwardness changes in this group had negative effects especially in the field of psychosocial functioning. The external view for DISE women is associated with high social status and is a tool of psychological impact on the environment. In DISE women signs of somatization with painful and histrionic displays, tension, nervousness, frustration and distrust for the environment, a sense of loneliness were present in the psycho-emotional sphere. For DISE patients personality and behavioral patterns such as demonstrativity, aggressiveness, emotional lability, tendency to confrontation, distancing, inability to positively overestimate stressful situation that became the basis for formation psychological adaptation were typical. Also significant signs of psychological maladjustment took place in their interpersonal and social interaction. Conclusions. In psychogenesis of mental disorders in DISE patients imbalance and conflict interaction with the environment caused by personal patterns rigidity, low self-reflection were the main factors of adaptation disturbances. Psychological help for DISE cosmetological patients should be focused on mental stress reduction, psychological self-regulations increase, unadaptive personality and behavioral patterns correction, formation of communication strategies aimed on maintaining harmonious interpersonal relationships, communicative competence improvement, interpersonal tolerance, non-conflict interaction.